HUBUNGAN BUDAYA DAN NILAI ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. PARAMOUNT LAND GADING SERPONG - Masrudin Masrudin (Universitas Sains dan Teknologi Komputer, 2022)
Organizational culture is an important thing to consider in human resource management. In addition, corporate values ​​are a collection of values ​​and culture that form the basis and foundation of the company in forming systems, processes, policies, and strategies in running the company. Therefore, to measure the performance of an organization should be measured in the work of its employees. To achieve or assess performance, there are dimensions that become benchmarks including quality, namely the level of error, damage,..precision. accuracy austerity neatness frugality nicety punctilio. Quantity is the number of jobs produced. This study aims to determine the influence of corporate culture and values ​​on employee performance at PT. Paramount Land Gading Serpong. Data analysis using Kendall's Tau. The results of the study through the kendall's Tau test that cultural variables were positively and significantly related to employee performance. While the value variable has a positive and significant relationship with employee performance.